2023
DOI: 10.1001/jamanetworkopen.2023.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Immersive Virtual Reality Intervention on Pain and Anxiety Among Pediatric Patients Undergoing Venipuncture

Abstract: ImportanceVenipuncture is one of the most painful and distressing procedures experienced by pediatric patients. Emerging evidence suggests that providing procedural information and distraction using immersive virtual reality (IVR) may reduce pain and anxiety among children undergoing needle-related procedures.ObjectivesTo examine the effects of IVR on reducing the pain, anxiety, and stress experienced by pediatric patients undergoing venipuncture.Design, Setting, and ParticipantsThis 2-group randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
0
12
1
3
Order By: Relevance
“…The IVR arm provided visual and auditory stimuli alongside procedural information tailored to age via a head-mounted display. Pain and anxiety were assessed using reliable and validated self-scoring systems: Faces Pain Scale–Revised and Visual Analogue Scale 4…”
Section: Effects Of An Immersive Virtual Reality Intervention On Pain...mentioning
confidence: 99%
“…The IVR arm provided visual and auditory stimuli alongside procedural information tailored to age via a head-mounted display. Pain and anxiety were assessed using reliable and validated self-scoring systems: Faces Pain Scale–Revised and Visual Analogue Scale 4…”
Section: Effects Of An Immersive Virtual Reality Intervention On Pain...mentioning
confidence: 99%
“…However, music interventions may require interventionists to receive adequate professional training to develop tailored music experiences, which may be limited in some health care settings. Distraction approach interventions, such as videos, multifaceted programs, interactive games, virtual reality (VR), and low sensory stimulation, have also been studied in the context of managing anxiety, particularly in children undergoing medical procedures and surgical procedures . However, the evidence for their effectiveness in the adult population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, non-pharmaceutical interventions have been explored for procedural pain management, with virtual reality (VR) being one of these promising interventions [8]. Numerous studies have found that VR significantly decreases procedural pain and anxiety [9][10][11][12][13]. VR is hypothesized to have effective pain management by creating a 3-dimensional distraction that limit the user's perception of painful stimuli [14].…”
Section: Introductionmentioning
confidence: 99%